DRA contingencies promote improved tolerance to delayed reinforcement during FCT compared to DRO and fixed‐time schedules. Issue 3 (7th April 2020) - Drifke, Melissa A.; Tiger, Jeffrey H.; Lillie, Madelynn A.
Abstract : Following Functional Communication Training (FCT), clinicians often gradually expose newly taught communicative responses to delayed reinforcement contingencies to prepare clients for the normative environment in which requests are frequently reinforced after a delay. The introduction of delays may result in the resurgence and maintenance of problem behavior and the weakening of the newly trained communicative response. The current study compared delay tolerance with three individuals diagnosed with intellectual and developmental disabilities when reinforcement for the functional communication response (FCR) was delivered following (a) the passage of time, (b) the omission of problem behavior, or (c) the occurrence of an alternative behavior. We measured delay tolerance in terms of minimizing problem behavior and maintaining efficient FCRs. Outcomes support requiring alternative responding during delays to attain optimal treatment results.